Ox-Lp(a) transiently induces HUVEC autophagy via an ROS-dependent PAPR-1-LKB1–AMPK–mTOR pathway. Issue 1 (November 2015) - Li, Guo-hua; Lin, Xiao-long; Zhang, Hai; Li, Shuang; He, Xing-lan; Zhang, Kai; Peng, Juan; Tang, Ya-ling; Zeng, Jun-fa; Zhao, Yue; Ma, Xiao-feng; Lei, Jian-jun; et al.
Abstract: Oxidised lipoprotein(a) [oxLp(a)] is considered as a more potent arteriosclerotic factor than native Lp(a). However, the molecular mechanisms underlying this potency remain unclear. Reactive oxygen species (ROS) possibly act as intracellular second messengers that participate in autophagy stimulation. In this study, the effect of oxLp(a) on endothelial cell autophagy was determined. The mechanism and effect of autophagy on endothelial cells were also investigated. Results showed that oxLp(a) could induce autophagy depending on the generation of cellular ROS. Superoxide dismutase, an antioxidant, could inhibit oxLp(a)-induced autophagy in human umbilical vascular endothelial cells. Furthermore, poly(adenosine diphosphate-ribose) polymerase-1 (PARP-1)-liver kinase B1 (LKB1)-adenosine monophosphate-activated protein kinase (AMPK)-mammalian target of rapamycin (mTOR) and LKB1–AMPK–mTOR pathways are involved in oxLp(a)-induced autophagy. These pathways are also dependent on ROS. Thus, oxLp(a) induced autophagy via LKB1–AMPK–mTOR and PAPR-1-LKB1–AMPK–mTOR pathways, which are dependent on ROS generation. Highlights: oxLp(a) was involved in HUVEC autophagy via the LKB1–AMPK–mTOR and PARP-1LBP1-AMPK-mTOR signalling pathways. oxLp(a)-induced autophagy depended on the production of intracellular ROS. Moreover, autophagy may participate in protecting endothelial cells to a certain extent when the cells were treated with oxLp(a).